PENINGKATAN MINAT BACA SISWA KELAS XII TATA BUSANA SMK DARUSSALAM DENGAN PROGRAM AKSI BACA PAKSA INDONESIA (ABPI) TAHUN 2021/2022 - Syafi’ Junadi; Fatma Nurul Widad (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
Learning to read has a very important role in learning Indonesian. All educators hope that their students can master reading skills. By reading students can broaden their horizons of knowledge. With the holding of the Indonesian Forced Reading Action program directs a student so that reading can become a culture and even a hobby. The hypotheses in this study are: 1) By holding the Indonesian Forced Reading Action program, students develop more interest in reading and students' interest in reading it without being told, 2) Before implementing the Indonesian Forced Reading Action program students had no interest in reading. knowing the world of reading, this is due to a lack of encouragement for oneself and the local environment, 3) after the Indonesian Forced Reading Action program was held, students became more interested in the world of reading. In this quantitative descriptive research, researchers will describe something. Descriptive research can involve the use of a questionnaire that will be a sample of increasing students' interest in reading. The hope is that students can develop their interest in reading by holding the Indonesian Forced Reading Action program. The questionnaire results from the researcher tested the validity, reliability, and normality at a significance level of 0.05 in the r table for 28 respondents with a result of 0.374. The Cronbach Alpha value of the X variable is 0.789, while the Y variable is 0.780, each of these variables shows a high increase in reading interest.